1971
DOI: 10.1172/jci106686
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the responsiveness of human subjects to human growth hormone

Abstract: A B S T R A C T The effect of human growth hormone (HGH) on the N, P, Na, and K balance, and on the body weight (BW) of three groups of subjects was measured. In group I were nine cases (age 6-69) with HGH deficiency; in group II, eight cases (age 9-79) with normal endogenous HGH; in group III, four cases with myotonic dystrophy (age 45-51). After a 7 day control period, the hormone was administered for 7 days. Each subject was tested with three doses of HGH: dose A, 0.0168 U/kg BW"' per day; dose B, 0.0532 U/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 21 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…pituitary hormones. Criteria for establishing deficiency of HGH, adrenocorticotropin, thyroid-stimulating hormone, gonadotropins, or antidiuretic hormone were as described before (1). Replacement doses for these deficiencies were: cortisol, 15-25 mg daily, administered at either 7 a.m. or 10 p.m. as specified; thyroxine, 0.2-0.3 mg daily given at 8 am.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…pituitary hormones. Criteria for establishing deficiency of HGH, adrenocorticotropin, thyroid-stimulating hormone, gonadotropins, or antidiuretic hormone were as described before (1). Replacement doses for these deficiencies were: cortisol, 15-25 mg daily, administered at either 7 a.m. or 10 p.m. as specified; thyroxine, 0.2-0.3 mg daily given at 8 am.…”
Section: Methodsmentioning
confidence: 99%
“…As indicators of response, we measured increments in daily balances of N, P, Na, and K and in body weight (BW). The results of these ex-1 Previous studies (1,3) have shown that both categories are 5-10 times more responsive to the anabolic effects of HGH than normal individuals. The minimal effective dose for the anabolic effect of HGH in normals is 0.168-0.532 U/kg BW3/' daily, compared to 0.0532-0.168 U/kg BW3'4 for the patients cited.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…For this reason, before the availability of a growth hormone RIA, improvement in nitrogen balance after growth hormone administration was used routinely for diagnosis of growth hormone deficiency and for assessment of therapeutic response (1 3-22). Even after the measurement of plasma growth hormone concentration became practical, testing the subject's nitrogen retention response to growth hormone administration remained a clinical and investigative tool (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%